Impacts of external price shocks on Malaysian macro economy: An applied general equilibrium analysis - Abul Quasem Al-Amin; Chamhuri Siwar; Abdul Hamid Jaafar (Colegio de Economistas de A Coru\~na, 2008)
This paper examines the impacts of external price shocks in the Malaysian economy. There are three simulations are carried out with different degrees of external shocks using Malaysian Social Accounting Matrix (SAM) and Computable General Equilibrium (CGE) analysis. The model results indicate that the import price shocks, better known as external price shocks by 15% decreases the domestic production of building and construction sector by 25.87%, hotels, restaurants and entertainment sector by 12.04%, industry sector by 12.02%, agriculture sector by 11.01%, and electricity and gas sector by 9.55% from the baseline. On the import side, our simulation results illustrate that as a result of the import price shocks by 15%, imports decreases significantly in all sectors from base level. Among the scenarios, the largest negative impacts goes on industry sectors by 29.67% followed by building and construction sector by 22.42%, hotels, restaurants and entertainment sector by 19.45%, electricity and gas sector by 13.%, agriculture sector by 12.63% and other service sectors by 11.17%. However significant negative impact goes to the investment and fixed capital investment. It also causes the household income, household consumption and household savings down and increases the cost of livings in the economy results in downward social welfare.
Keywords: 330; trade liberalization; external price shocks; applied general equilibrium analysis; malasian economy